Effects of aflibercept on primary RPE cells: toxicity, wound healing, uptake and phagocytosis. Issue 10 (17th July 2014) - Klettner, Alexa; Tahmaz, Nihat; Dithmer, Michaela; Richert, Elisabeth; Roider, Johann
Abstract : Background/aim: Anti-VEGF treatment is the therapy of choice in age-related macular degeneration, and is also applied in diabetic macular oedema or retinal vein occlusion. Recently, the fusion protein, aflibercept, has been approved for therapeutic use. In this study, we investigate the effects of aflibercept on primary RPE cells. Methods: Primary RPE cells were prepared from freshly slaughtered pigs' eyes. The impact of aflibercept on cell viability was investigated with MTT and trypan blue exclusion assay. The influence of aflibercept on wound healing was assessed with a scratch assay. Intracellular uptake of aflibercept was investigated in immunohistochemistry and its influence on phagocytosis with a phagocytosis assay using opsonised latex beads. Results: Aflibercept displays no cytotoxicity on RPE cells but impairs its wound healing ability. It is taken up into RPE cells and can be intracellularly detected for at least 7 days. Intracellular aflibercept impairs the phagocytic capacity of RPE cells. Conclusions: Aflibercept interferes with the physiology of RPE cells, as it is taken up into RPE cells, which is accompanied by a reduction of the phagocytic ability. Additionally, it impairs the wound healing capacity of RPE cells. These effects on the physiology of RPE cells may indicate possible side effects.